The Factors associated with non-adherence to HPV vaccine among health science students - de Oliveira Guimarães, Amanda; Nascimento dos Santos, Alice; Santos de Toledo , Bianca; Lopes de Carvalho, Marcelo; Fortunato Pedroso , Charlise; de Pinho Santos , Thays Angelica; de Jesus Goncalves , Ingrid Aline; da Silva Cintra de Paula, Hellen; Silva Pinheiro, Raquel; Apolinário de Araújo, Lyriane (Journal of Health Care, 2021)
Introduction: Adolescents and young adults are considered vulnerable groups to human papillomavirus (HPV) infection, due to risky sexual behaviors such as greater number of partnerships and inconsistent condom use. In Brazil the HPV vaccine has been available since 2014, however adherence is still below expectations. Objectives: To identify factors associated with non-adherence to the vaccine, vaccination status and knowledge about HPV among health science students in Goiânia. Materials and Methods: Cross-sectional study, carried out with 131 participants. A questionnaire was applied containing questions about sociodemographic characteristics, knowledge of HPV and vaccination status. Poisson regression was performed to identify predictors of non-adherence to vaccination. Results: Most students were female (81.7%), with a mean age of 17 years. The HPV knowledge score was 67.4%. Of the total, 59 (45.0%) declared themselves vaccinated. The factors associated with non-adherence to the HPV vaccine were age over 18 years, male and parents who had at most eight years of formal study. Conclusion: The findings of this study reinforce the need for intersectoral actions to promote vaccination, involving educational institutions and health units, in order to provide a dialogue between students, parents, health professionals and teachers. It is believed that access to qualified information can contribute to changing behavior and improving decision making, leading students to reflect on their attitudes and risks inherent to HPV infection.